Mixing analysis of nutrients, oxygen and inorganic carbon in the Canary Islands region - Pérez, Fiz F.; Mintrop, L.; Llinás, O.; González-Dávila, Melchor; Castro, Carmen G.; Álvarez, Marta; Körtzinger, Arne; Santana-Casiano, Magdalena; Rueda, María José; Ríos, Aida F. (Journal of Marine Systems, 2001)
19 páginas, 5 figuras, 2 tablas We show the distribution of nutrients, oxygen, total dissolved inorganic carbonŽCT.and total alkalinityŽAT.along three sections close to the Canary Islands, between 188W and the African coast during Meteor 37r2 cruiseŽJanuary 1997. From the thermohaline properties of Eastern North Atlantic Central WaterŽENACW., Mediterranean WaterŽMW., Antarctic Intermediate WaterŽAAIW.and North Atlantic Deep WaterŽNADW., a mixing model has been established based on the water mass description. It can explain most of the variabilities found in the distribution of the chemical variables, including the carbon system, and it is validated through the use of conservative chemical variables like ‘NO.’ From nutrients, oxygen, AT and CT, the chemical characterisation of the water masses was performed by calculating the concentration of these variables in the previously defined thermohaline end-members. The relative variation of nutrient concentrations, resulting from the regeneration of organic matter, was estimated. Close to the African shelf-break, a poleward undercurrent conveying as much as a 11% of AAIW was observed only in the southern sectionŽ28.58N. From the chemical and thermohaline properties of the end-members, a comparison with data from other oceanic regions was made in respect to conservative chemical variablesŽ‘NO’. In addition, a north–south gradient in the ventilation pattern of water masses is observed from the residuals of the model Processing and the modelling work were supported by the MAS3-CT96-60 project of EU. Peer reviewed